Othering of Full-Time and Volunteer Women Firefighters in the Canadian Fire Services - Gouliquer, Lynne; Poulin, Carmen; McWilliams, Jennifer (Qualitative Sociology Review, 2020)
Being discriminated against because of factors such as gender, ethnicity, age, sexual orientation, and stature (i.e., height and weight) has been a common experience for women in traditionally men-dominated/identified occupations. Although women’s representation has risen in other men-dominated domains (Hughes 1995), within firefighting their presence remains extremely low in Canada (4.4% [Statistics Canada 2017]). Women firefighters mostly operate in a patriarchal context; they are often ignored, harassed, and treated poorly due to an intersectionality of factors (Paechter 1998). Thus far, most research has taken place in the US, UK, and AUS. In the present Pan-Canadian study, we examined the experiences of volunteer and career women firefighters (N=113). The Psycho-Social Ethnography of the Commonplace methodology (P-SEC [Gouliquer and Poulin 2005]) was used. With this approach, we identified several practices, both formal and informal (e.g., physical and academic standards, gender roles), which resulted in women feeling the effect of the intersection of gender and firefighting. Results indicated that women firefighters experience “Othering” manifesting itself in a variety of ways such as discrimination, hostility, and self-doubt. This paper focuses on Canadia women firefighters and ends with social change and policy recommendations to better their reality.